Academic mobility of students as a factor in sustainability in higher education (the example of the Republic of Kazakhstan) - A. M. Maratova; N. V. Yakovenko; G. E. Kairlieva; Yu. A. Afonin; K. T. Utegenova; V. V. Voronin (Юг России: экология, развитие)
Aim. To reveal the features of the process of academic mobility as a factor in the  sustainability of the higher education system (in the example of the Republic of  Kazakhstan). Discussion. The organisation of student academic mobility is determined by the  students striving to move for the purpose of academic exchange in the educational  space and social adaptation in the framework of this process. The modeling of the  organisation of academic mobility of students in higher education is a specific cognitive method in which the object of study is imitated in a model. A model of the academic mobility of students is presented in this article together with an exposition of  its structural components and functionality.   Conclusion. In the current situation in Kazakhstan outgoing academic mobility is of  the greatest priority and acts as a mechanism to develop the intellectual potential  and skills of the population. Incoming student mobility in Kazakhstan occupies a less  significant position because of the weak material and technical base of Kazakhstan  universities, underdeveloped services and infrastructure, limited abilities to provide  education in English and visa restrictions. All this negatively affects the competitiveness of the Kazakhstan higher education system. In considering the indicators of  international student exchange in the states of the Customs Union of the Eurasian  Economic Union, it should be noted that outgoing mobility in Kazakhstan is more  than two times higher than incoming, which impacts on the competitiveness of  Kazakhstan universities in international mobility ratings. Effective organisation of  the academic mobility of students in Kazakhstan will contribute to an increase in the  influx of foreign students to its universities. It will also contribute to the formation  of competitive specialists and their participation in the development of an advanced  society and a knowledge‐based economy in the context of globalization, internationalisation and sustainable development.